Radioecological studies of the main naturally occurring radionuclides in the area of Gela Phosphate Industry (Italy) through radioanalytical separation and measurement techniques. (June 2022) - Jia, Guogang; Buchetti, Monica; Conti, Daniela; Magro, Leandro; Mariani, Sara
Abstract: Radioecological studies have been carried out in area of Gela Phosphate Industry. As a part of the project, some achievements have been described in the paper, including: (1) determination of the activity concentrations of 210 Po, 210 Pb, uranium, and radium isotopes in phosphogypsum, phosphoric acid, soil, and marine sediment, (2) inventory estimation of the NORM in the residual product and by-product, and (3) the radioecological investigation and evaluation on the NORM contamination in the sea area of Gela. The obtained data showed that the 210 Po, 210 Pb, uranium, and radium isotope contamination due to discharge of phosphogypsum from 1960s to 1990s is not observable through sediment analyses. Highlights: The concentrations of 210 Po, 210 Pb, 212 Pb, uranium and thorium isotopes in phosphogypsum and sediment were determination. The inventory of the NORM in the residual phosphoric acid and by-product was estimated. The radioecological impacts of the NORM contamination on the sea area of Gela were assessed.